O-012 The Effect of Pipeline Embolisation Device on Intra-Aneurysmal Pressures: In-Vitro Study. (14th July 2013) - Gonzalez, F; Roszelle, B; Babiker, H; Frakes, D
Abstract : Introduction: Pipeline (PED) has become commonly used to treat cerebral aneurysms, studies have found that 1% of cases that use the device result in devastating subarachnoid haemorrhage due to aneurysm rupture. The cause of these complications is still unclear, and some hypothesise it may be due to the effect the PED has on the intra-aneurysmal pressure. Materials and Methods: We performed in vitro studies on two patient-specific models of cerebral aneurysms (fig 1). While both aneurysms were similar in size they had different fundamental geometries, as the first was a basilar tip and the other a side wall. In order to measure the intra-aneurysmal pressure a 0.42 mm tap was drilled into the model and a 0.40 mm micro-catheter was thread into the hole and attached to a pressure transducer (Harvard Apparatus, Holliston, MA, USA). pressure measurements were acquired and collected with Labview Signal Express (National Instruments, Austin, TX, USA). Along with the intra-aneurysmal pressure, pressure measurements were also collected at the inlet and outlet of the model. In conjunction with the pressure measurements, particle image velocimetry, a flow visualisation technique, was used to observe the haemodynamic flow patterns within the aneurysm. Results: Results from the sidewall aneurysm showed that the deployment of the PED led to a dampening of the pulsatile waveform within the aneurysm. However, the PED also led to an increase in average intra-aneurysmal pressure of over 7 mmHg (fig. 2). In contrast, the BTA model did not show an increase in intra-aneurysmal pressure. This difference is likely related to the fact that the sidewall aneurysm is a closed system (only one inlet and outlet), while the BTA has an additional untreated outflow. In fact the BTA model also showed an increase in pressure drop across the untreated vessel during PED deployment, which indicates that the blood flow is being directed in that direction. The flow visualisation patterns of both models indicated a reduction in the velocities within the aneurysm, indicating that the PED is leading to reductions in fluid dynamic activity, making the increase in pressure of even greater interest. Conclusion: The results of this study, while preliminary, give insight into the intra-aneurysmal pressure changes associated after deployment of the PED. Our results indicate that the PED does lead to haemodynamic changes in pressure within the aneurysm that could lead to ruptured. Disclosures: F. Gonzalez: None. B. Roszelle: None. H. Babiker: None. D. Frakes: None.